Correlation between prediabetes and coronary artery disease severity in patients undergoing elective coronary angiography - Ahmed Muhammed (The Egyptian Heart Journal, 2019)
Abstract Background Diabetes is a chronic disease that is responsible for a high rate of morbidity and mortality which can be attributed to atherosclerosis and cardiovascular disease. Diabetes is heralded by prediabetes which not only indicates a higher risk of developing diabetes but also increases the burden of cardiovascular disease. The objective was to observe the effect of prediabetes on the severity of coronary artery disease in patients undergoing elective coronary angiography. Seven hundred and thirty-one patients were admitted for elective coronary angiography and/or PCI starting from September 2017 to August 2018. Patients were divided into group A (normoglycemic group, N = 228), group B (prediabetes group, N = 177), and group C (diabetic group, N = 326). Coronary artery disease (CAD) severity including number of vessels affected and atherosclerotic burden by Gensini score were compared among different groups. Results The number of vessels affected as well as left main (LM) disease was higher in the prediabetes group when compared to the normoglycemic group (P,=0.001, P = 0.009, respectively) and was comparable to the diabetes group (P = 0.4, P = 0.6, respectively). Prediabetes showed a Gensini score higher than the normoglycemic group (P = 0.0001) with no significant difference when compared to the diabetic group (P = 0.9). Conclusion Prediabetes is associated with high atherosclerotic burden and coronary artery disease complexity that is similar to diabetic than normoglycemic individuals.